Standarisasi Pengelolaan Otonomi Akademik, Otonomi Keuangan dan Struktur Organisasi PTN-BH dalam Perspektif Teori Perundang-Undangan - Yoga Firdausi; Bachrul Amiq; Cita Yustisia Serfiyani (Jurnal Hukum Lex Generalis, 2026)
The regulation of State Universities with Legal Entity Status (PTN-BH) through Government Regulations as university statutes raises a theoretical issue within the framework of legislative theory, particularly concerning the boundary between the function of Government Regulations as implementing legislation and their role as instruments governing fundamental institutional matters. Existing studies on PTN-BH have primarily focused on university autonomy and governance, while limited attention has been given to the legitimacy of Government Regulations serving as university statutes within the hierarchy of laws and regulations. This study aims to analyze the legal position of Government Regulations as PTN-BH statutes and their implications for academic autonomy, financial autonomy and organizational structure. Employing normative legal research with statutory, conceptual and comparative approaches, the study finds that Government Regulations on PTN-BH do not merely function as delegated legislation but also contain constitutive norms governing organizational structures, institutional authority and university governance. This condition raises concerns regarding the compatibility between the type of regulation and its substantive content within Indonesia’s legislative system. Therefore, regulatory reform is needed through a limited standardization model that establishes basic norms on academic autonomy, financial autonomy and organizational structure at the statutory level, while leaving technical arrangements to the respective PTN-BH statutes.